ANALYSIS OF FARMERS’ FOOD DISTRIBUTION FROM THE VIEWPOINT OF THE COMMUNITY THAT SUPPORTS AGRICULTURE - CSA CAJAZEIRAS - Igor de Sousa Abreu, Francisco; Rodrigo de Abreu Coura, Jefferson; Munoz Cevada Jeronymo , Caroline (Journal of Interdisciplinary Debates, 2022)
In view of the importance of family farming for everyone, being the best source of access to organic and high nutritional value foods, it is necessary to facilitate the dissemination of them to the population. However, observing the difficulties of the farmers due to the lack of knowledge of how to deal with the logistics and transport of this merchandise, this work aims to observe and analyze the methodologies used CSA (Community that Sustains Agriculture) of Cajazeiras - Paraíba that has as paper, educate farmers, improve the contact between them and the consumer and consequently improve their quality of life in their work.